If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -2 = 2(2x + -17) Reorder the terms: -2 + X = 2(2x + -17) Reorder the terms: -2 + X = 2(-17 + 2x) -2 + X = (-17 * 2 + 2x * 2) -2 + X = (-34 + 4x) Solving -2 + X = -34 + 4x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + X = -34 + 2 + 4x Combine like terms: -2 + 2 = 0 0 + X = -34 + 2 + 4x X = -34 + 2 + 4x Combine like terms: -34 + 2 = -32 X = -32 + 4x Simplifying X = -32 + 4x
| -6a+3(11-8a)-2=0 | | 7(4-x)=112 | | 8/13=y/12 | | -7x+57=12-7(x+8) | | X^2=5n | | Y+-5=10y-14 | | 4x^2+38=-34 | | 12y+4x=12 | | 21-87= | | x(x^2-8x+3)= | | 5(2n+7)=19 | | x-9-5=7-x-76 | | 3-11=-8 | | -34=-2y+3y | | 4+2s=3s-7 | | x^2+4x+18=40 | | 3x^2+23=-13 | | 7n-16n+4=0 | | -a+7(1+3a)-20=0 | | 2x+40=.182x | | 18x+3=10x-45 | | -(m-6)=3m+4 | | x^2+4x-18=40 | | 6x+8-2=-24 | | 12/m-3 | | -5x+16+-8(x+1)=6x | | 2x^2-3y^2=12 | | 4m/m-3 | | -3+7=-5 | | -6x-x+10=15-7x | | 1-n-5+16=-n-2n | | (9v+36)(v^2-6v+5)=0 |